Activated Protein C Induces Endoplasmic Reticulum Stress and Attenuates Lipopolysaccharide-Induced Apoptosis Mediated by Glycogen Synthase Kinase-3β. (28th May 2012) - Luo, Liang; Lv, Tangfeng; Wang, Qian; Zhang, Ting; Gu, Xiaoling; Xu, Feng; Song, Yong
Abstract : This study investigated the relationship between antiapoptotic activities induced by activated protein C and endoplasmic reticulum stress. In this study, it was observed that activated protein C elicited a rise in glucose-regulated protein 78 and glycogen synthase kinase-3 β and inhibited apoptosis in human umbilical vein endothelial cells induced by lipopolysaccharide. Calcium inhibition did not alter the antiapoptotic effect of activated protein C. The antiapoptotic efficiency of activated protein C was reduced in human umbilical vein endothelial cells following treatment with glycogen synthase kinase-3 β -siRNA. In summary, activated protein C induced endoplasmic reticulum stress and attenuated lipopolysaccharide-induced human umbilical vein endothelial cell apoptosis mediated by glycogen synthase kinase-3 β .